Design, Synthesis and Molecular Docking Studies of (S)-1-(2-(substituted benzylamino)-3-methylbutanoyl)pyrrolidin-2-one analogues as GABA Mediated Anticonvulsant Agents - Afzal, Obaid; Agrawal, Gopal Prasad; Alotaibi, Ghadah Rashed Ghazi; Shatat, Raid Saleh Ali; Khalilullah, Habibullah; Ullah, Zabih; Rashid, Mohammad; Elkirdasy, Ahmed F; K, Benson Mathai (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Epilepsy is a deep rooted, partially curable brain illness that affects all individuals irrespective of ages and genders. Despite the discovery of various innovative antiepileptic drugs (AEDs), selectivity and toxicity issues remain. Materials and Methods: A series of (S)-1-(2-(substituted benzylamino)-3-methylbutanoyl)pyrrolidin-2-one analogues (5a-r) were synthesized and evaluated for their anticonvulsant activity. The analogues were screened by two gold standard methods, i.e., electroshock (MES) and chemoshock (scPTZ) seizure tests. In addition, the rotarod method was used to test motor impairment in all synthetic analogues for acute neurotoxicity. The paper also reports ADME prediction of all the 18 synthesized compounds, with each parameter discussed in detail. Furthermore, the GABA-A target protein was used in molecular docking experiments. Results: In the MES model, compounds 5e, 5h, 5k, 5l, 5o, and 5r were identified to be the most effective, while compounds 5j, 5k, 5l, 5o, and 5r were the most active against the scPTZ model. The majority of the synthesized analogues passed the neurotoxicity test, according to the findings. ADME prediction of the compounds exhibited good agreement with the in vivo outcomes. The results of molecular docking showed important interactions with TYR 62, ASN 85, ARG 114, ARG 129, and MET 115 at the active site of GABA-A and the results showed good agreement with in vivo results. Conclusion: The findings of the study indicated some of the compounds possessed excellent anticonvulsant activity without noticeable neurotoxicity. These compounds can be investigated further for the formation of newer/novel anticonvulsant agents.
Keywords: Pyrrolidine; Anticonvulsant activity; Molecular Docking; GABA-A; Toxicity; ADME prediction